2014
DOI: 10.2754/avb201483040379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding prefermented cereal product containing gamma-linolenic acid to broiler feed on production indicators and fatty acid profile of chicken breast

Abstract: Administration of Thamnidium elegans for effective utilization of agroindustrial materials (wheat bran) creates new perspectives for animal cereal diet enriched with fungal γ-linolenic acid (GLA). The aim of our study was to evaluate the effect of adding prefermented cereal product containing a high amount of gamma-linolenic acid into the feed on broiler chickens' performance, fatty acids profile and oxidative stability in chilled breast meat. Seventy eight COBB 500 oneday old broiler chicks were randomly divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
3
17
1
Order By: Relevance
“…The fermentation substrate, but mainly the lower filamentous fungi used, has a significant effect on the production of significant metabolites (PUFAs, antioxidants, and enzymes). In our previous experiments we did not notice such a significant decrease in arachidonic acid, but the ALA fraction was higher than in this experiment [ 30 , 36 ]. However, a different concentration (3 and 5%) was used in both experiments, and also different lower filamentous fungi ( Thamnidium elegans or Cunninghamella elegans ) were used for SSF and they produced only GLA.…”
Section: Resultscontrasting
confidence: 63%
“…The fermentation substrate, but mainly the lower filamentous fungi used, has a significant effect on the production of significant metabolites (PUFAs, antioxidants, and enzymes). In our previous experiments we did not notice such a significant decrease in arachidonic acid, but the ALA fraction was higher than in this experiment [ 30 , 36 ]. However, a different concentration (3 and 5%) was used in both experiments, and also different lower filamentous fungi ( Thamnidium elegans or Cunninghamella elegans ) were used for SSF and they produced only GLA.…”
Section: Resultscontrasting
confidence: 63%
“…It is effective in anti‐inflammatory and anticancer actions as well as in the treatment of atopic eczema, rheumatoid arthritis, multiple sclerosis, schizophrenia and premenstrual syndrome . Owing to its actions, many studies on GLA in animal feed have been carried out in order to improve the fatty acid profile of meat products . In the present research, it can be observed in Table that GLA values in bologna sausages increased significantly with the addition of Echium oil; the T25 and T50 products presented 29.47 and 45.42 g GLA kg −1 fat, equivalent to 7.38 and 11.35 g GLA kg −1 product, respectively.…”
Section: Resultsmentioning
confidence: 54%
“…orange peels, apple or pear pomace, sweet sorghum, etc.) can be enriched in PUFAs through solid or semi-solid state fermentation with PUFA producing microorganisms [4][5][6][7][8] and directly used as food and/or feed supplements.…”
Section: Introductionmentioning
confidence: 99%